Analisis Naskah Drama Lautan Bernyanyi Karya Putu Wijaya: Sebuah Kajian Strukturalisme Drama - Seni Melani; Salwa Sania Adawiah; Dalpa Nurmaulidah; Adita Widara Putra (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Literary works certainly have their own benefits, but to find out these benefits you must first analyze them with special studies, one of which is structural studies. Researchers conducted a structural study of literary works in the form of drama scripts. The researcher used the drama script